The burden of antimicrobial resistance in livestock: A framework to estimate its impact within the Global Burden of Animal Diseases programme - Sara Babo Martins; João Sucena Afonso; Christina Fastl; Benjamin Huntington; Jonathan Rushton (One Health, 2024)
In addition to affecting animal health and production, antimicrobial resistance (AMR) in livestock can have far-reaching social and economic consequences, including on human health and the environment.Given the diversity of data needs and the absence of standardised methodologies, the scale of antimicrobial use (AMU) and AMR's social and economic burden on livestock is complex to gauge. Yet, quantifying this impact can be an essential input for farm-level decision-making and, more widely, for policy development, public awareness, resource allocation to interventions and research and development prioritisation, particularly in a One Health context.This work proposes a conceptual framework to guide the assessment of the burden of AMU and AMR in livestock using the Global Burden of Animal Diseases (GBADs) approach. Its development identified and mapped critical socio-economic concepts in AMU and AMR in livestock and their relationships. The Animal Health Loss Envelope (AHLE), a monetary metric that sets a boundary for overall losses from health hazards and allows an understanding of the relative importance of health problems in livestock, was used as the metric in which the concepts and data needs for the AMU and AMR assessment were anchored. The proposed framework identifies pathways for losses and data inputs needed to estimate the burden of AMU and AMR within this wider envelope of losses. These include information on health expenditure and mortality and morbidity effects related to AMR in livestock.This work highlights the need for improved health and production data collection in livestock production as an essential stepping stone to accurately producing AMU and AMR burden estimates.